The School as A Learning Literacy of Folklore: Comparative Study of The Usa and Indonesia - Zikri, Ahmad; Gustiati, Nurhizrah; Rusdinal, Rusdinal; Ananda, Azwar (Indonesian Research Journal on Education, 2024)
This study aimed to evaluate the effectiveness of using folklore-based character education materials in improving reading literacy and social care understanding among elementary school students. Employing a comparative quantitative design, the research involved 74 students, divided into experimental and control groups, each consisting of 37 students. The experimental group received education materials integrating folklore, while the control group used standard print teaching materials. Data were collected through tests measuring reading literacy and social care understanding, both before and after the intervention. The results showed that the experimental group had an average reading literacy score of 69.07, higher than the control group's 58.94. In understanding social care, the experimental group also excelled with an average score of 77.37, compared to 66.99 in the control group. ANOVA tests revealed significant differences between the two groups, with an F Statistic of 13.46 and a P-value of 0.000464 for reading literacy, and an F Statistic of 19.71 and a P-value of 0.000032 for social care understanding. These findings indicate that the use of folklore-based education materials significantly contributes to improving reading literacy and social care understanding among students, demonstrating the potential of this approach in character education in elementary schools.